The Effectiveness of a Computerized Cognitive Rehabilitation Program on Executive Functions in Children With Externalizing Behavioral Disorders - Javidnia, Soroush; Rezaei , Saeed; Nikkhoo , Fatemeh (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to investigate the effectiveness of a computerized cognitive rehabilitation program on executive functions, including emotional control, attention shifting, behavioral control, and inhibition, in children with externalizing behavioral disorders.Methods and Materials: The present study employed a quasi-experimental design with a pretest–posttest control group structure. The statistical population consisted of children and adolescents with externalizing behavioral disorders who received psychological services in clinics located in Rasht during 2021. Using purposive sampling, 32 participants were selected and randomly assigned into experimental and control groups, with 16 participants in each group. Participants were matched based on age, gender, and intelligence level. Data collection instruments included the Eyberg Child Behavior Inventory (ECBI) and the Behavior Rating Inventory of Executive Function (BRIEF), Parent Form. The experimental group received a computerized cognitive rehabilitation intervention consisting of Lumosity and Peak cognitive training games across 20 sessions over a three-week period, while the control group received no intervention. Data were analyzed using descriptive statistics and one-way multivariate analysis of covariance (MANCOVA) in IBM SPSS Statistics version 26.Findings: The results of multivariate covariance analysis indicated significant differences between the experimental and control groups in executive function components after controlling for pretest scores. Significant improvements were observed in emotional control (F = 67.369, p < 0.001, η² = 0.706), attention shifting (F = 22.689, p < 0.001, η² = 0.448), behavioral control (F = 51.472, p < 0.001, η² = 0.648), and inhibition (F = 63.502, p < 0.001, η² = 0.694) in the experimental group. Multivariate test results also demonstrated a significant overall effect of the intervention on executive functioning variables, whereas no significant differences were found in the control group between pretest and posttest stages.Conclusion: The findings suggest that computerized cognitive rehabilitation is an effective intervention for improving executive functions in children with externalizing behavioral disorders.